2002
DOI: 10.1046/j.1460-9568.2002.02257.x
|View full text |Cite
|
Sign up to set email alerts
|

The rat ponto‐medullary network responsible for paradoxical sleep onset and maintenance: a combined microinjection and functional neuroanatomical study

Abstract: The neuronal network responsible for paradoxical sleep (PS) onset and maintenance has not previously been identified in the rat, unlike the cat. To fill this gap, this study has developed a new technique involving the recording of sleep-wake states in unanaesthetized head-restrained rats whilst locally administering pharmacological agents by microiontophoresis from glass multibarrel micropipettes, into the dorsal pontine tegmentum and combining this with functional neuroanatomy. Pharmacological agents used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
319
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(348 citation statements)
references
References 51 publications
22
319
1
6
Order By: Relevance
“…Application of the cholinergic agonist carbachol to this area in the cat causes, at short latency, a pharmacologically induced state virtually indistinguishable from REM sleep, including the muscle atonia component (Mitler and Dement, 1974;Baghdoyan et al, 1987;Vanni-Mercier et al, 1989;Yamamoto et al, 1990). In the rat, carbachol does not normally cause a REM-like state when injected into the SubC but a state similar to REM can be induced by application of the GABA A receptor antagonists, bicuculline and GABAzine (Boissard et al, 2002;Pollock and Mistlberger, 2003). (Thakkar et al, 1999).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of the cholinergic agonist carbachol to this area in the cat causes, at short latency, a pharmacologically induced state virtually indistinguishable from REM sleep, including the muscle atonia component (Mitler and Dement, 1974;Baghdoyan et al, 1987;Vanni-Mercier et al, 1989;Yamamoto et al, 1990). In the rat, carbachol does not normally cause a REM-like state when injected into the SubC but a state similar to REM can be induced by application of the GABA A receptor antagonists, bicuculline and GABAzine (Boissard et al, 2002;Pollock and Mistlberger, 2003). (Thakkar et al, 1999).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Early transection studies by Jouvet and coworkers in the cat identified the pons as being critical for REM sleep (Jouvet, 1962). Further investigation by the Jouvet group and others identified a region ventral to the locus coeruleus (LC), lateral to the midline and mediodorsal to the trigeminal motor nucleus which plays a critical role in at least two aspects of REM sleep, namely muscle atonia and PGO spikes (Mouret et al, 1967;Marks et al, 1980;Baghdoyan et al, 1984;Morrison, 1988;Yamamoto et al, 1990;Boissard et al, 2002). In the cat this region has been called the peri-LC, subcoeruleus alpha and subcoeruleus whereas in the rat it encompasses the regions termed dorsal subcoeruleus (SubCD) and subcoeruleus alpha part (SubCA) by Paxinos and Watson (Paxinos and Watson, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fos staining refined the understanding by implicating a specific pontine cell population, in rodents an area named the sublaterodorsal nucleus (SubC), as the point of induction and maintenance of REM sleep and REM sleep atonia [8][9][10][11]. The SubC is a small pontine nucleus representing a mix of glutamateric and GABAergic neurons; located ventral to the locus coeruleus (LC), medial to the trigeminal motor nucleus (MO5) and ventromedial to the laterodorsal tegmental nucleus (LDT) and the parabrachial nucleus (PB).…”
Section: Section 12 -Rem Sleep Generationmentioning
confidence: 99%
“…Anterograde tracing studies have shown that one subset of glutamatergic SubC REM-on neurons have projections downstream to the alpha and ventral gigantocellular (GiA/GiV) neurons as well as spinal interneurons of the ventral horn [10]. These descending pathways have been shown to play a role in REM atonia [30,31].…”
Section: Section 12 -Rem Sleep Generationmentioning
confidence: 99%